Impact of Various Factors on the Identification of Inertia in Power Systems - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2021)
The growing integration of renewable energies has displaced synchronous generation, reducing the inertia of power system. The increasing availability of data from SCADA control rooms and synchrophasor systems has opened the opportunity for the development of purely data-based inertia estimation methods. The identified inertia, independent of the method, seems to be poorly related with net load. This work presents the existence of this phenomenon in different electrical systems and looks for reasons for its existence. Through simulations, preliminary results are shown, showing the inertial relationship with the net load in the Chilean power system and the influence of the economic operation on the identified inertia value. © 2021 IEEE.